NILAI-NILAI PENDIDIKAN KARAKTER DALAM PERMAINAN TRADISIONAL SUKU ANEUK JAMEE - Rika Kustina (Master Bahasa, 2022)
This research lifts about traditional games that slowly shifted by changes in times, to resulted with the decline in the character of the nation's children. The traditional game studied was the game of Jamee Aneuk tribe in Labuhan Haji, South Aceh. This study aims to lift traditional games and describe the meaning of the character's education value contained in the game. Data in this study are some traditional games that use verbal media, with data speculation used using Jamee. Data analysis techniques use Miles and Huberman models. The results of the study show that there are several character education values, namely the value of honesty, tolerance values, disciplinary values, democratic values, hard work values, values of respect for achievement, social care value and responsible value. Based on the results of the above, the author suggested that this research be a reference, exciting scientific insight and reading enhancer.